THE EFFECTIVENESS OF USING MOODLE TO THE STUDENTS ATTITUDE IN EFL CLASSROOM - Rahayu, Puji; Rahman, Dita Aulia; Mustofa, Mutmainnah (Premise: Journal of English Education and Applied Linguistics, 2022)
Since classroom-based instruction has been replaced by a hybrid of in-person interaction and online study, technology has transformed how knowledge is transferred and acquired. During covid-19 pandemic to overcome the situation, Learning From Home (LFH) is being implemented in all majors. This day, Moodle which is one of Learning Management System (LMS) is mostly used during online learning as a learning platform. The aim of this research is to investigate the students’ attitude in learning English by using Moodle. The researcher done this research by using descriptive qualitative research method. In collecting the data, the researcher has interviewed the students of University of Islam Malang as the subject. After that, the researcher analyzes and describes the result of interview sessions. However, it was found that the students of University Islam Malang have a positive attitude towards using Moodle which can improve their grade and motivation in learning English.